The Optimization of English Teaching with the Task-Based Language Teaching Method to Improve Speaking Ability for Eleventh Grade Students: Penelitian - Epita Sari; Eka Agustina; M. Muklas (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aimed to examine the optimization of English teaching through the Task-Based Language Teaching (TBLT) method to improve the speaking ability of eleventh-grade students at Vocational High School Nurul Huda Sukaraja. The research employed a quasi-experimental design with two groups: an experimental group taught using the TBLT method and a control group taught using conventional methods. Data were collected through oral tests and analyzed using SPSS version 25. The results revealed that the TBLT method significantly enhanced students’ speaking performance. Statistical analysis through the independent t-test showed a significant difference between the experimental and control groups (p = 0.001 < 0.05). These findings suggest that TBLT is an effective approach for fostering students’ speaking competence and communicative confidence in EFL classrooms.